Effect of phosphoric rock on the chemical, microbiological and enzymatic quality of poultry, equine and cattle manure compost mix - Luis Paez; Jose Garcia; Joel Parra; Leonardo Lozano Jacome (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Phosphorus (P) is one of the key elements in the agricultural sector, allowing improved production yields. Phosphate rock is a natural source of phosphorus; however, its low reactivity limits the release of P available to plants in the short term, conditioning its application in a direct way. Research was conducted to determine the effect of phosphate rock on a manure compost mix by measuring its availability of P and its microorganism activity.   Method Cattle manure, equine manure, and poultry manure from three provinces of the department of Boyacá, Colombia, were moistened up to 60% with fermented mineralized liquid and composted with different proportions of phosphate rock. After 60 days of composting, the mineral content and microorganism activity were measured.Results This study revealed three notable results. First, the addition of phosphate rock led to an increase in total and available P and a decrease in water-soluble phosphorus and inhibitory effects of phosphatase activity. Second, composting with the three manures resulted in microorganism activity levels ​​higher than 700*104 CFU, exceeding the NTC’s definition of an inoculant fertilizer in the agricultural process. Third, a strong positive relationship was found between ammonia-oxidizing bacteria and PBII, a medium correlation was found between PSM and TP, and a negative correlation was found between pH and PT.Conclusion Composting manure with phosphoric rock could be a low-cost source of macronutrients, minerals, and microorganisms to promote soil health and crop yields.